Satisfaction of external customers. A case study of an indoor swimming pool - Sánchez García, C.; González Carcelén, C. M.; López Sánchez, G. F.; Díaz Suárez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
Nowadays, aquatic activities are very important because they are very demanded by the population and sport users. The aim of this study was to carry out a case study, assessing the satisfaction of the users of the public swimming pool of Puente Tocinos (Region of Murcia). For this purpose, the sample was composed of 44 users (28 females and 16 males), with a mean age of 27.73 years (SD 14.5), ranging from 14 to 64 years. All participants completed the "Sports Services Assessment Questionnaire (EPOD2)". The data obtained were analyzed using SPSS 23 software. The results showed a high overall satisfaction, without significant differences according to sex and age. The highest values of satisfaction were given in the dimensions: monitors, activities offered, relationship between the staff of the facility, and quality-price ratio. The lowest values corresponded to the cleanliness and spaciousness of the dressing rooms of the facility. It is recommended to work in the expansion and cleaning of spaces.